The role of medial ligaments and tibialis posterior in stabilising the medial longitudinal foot arch: a cadaveric gait simulator study. Issue 7 (October 2022) - Robberecht, Joris; Shah, Darshan S.; Taylan, Orçun; Natsakis, Tassos; Vandeputte, Geoffroy; Vander Sloten, Jos; Jonkers, Ilse
Abstract: Background: Debate exists whether adult acquired flatfoot deformity develops secondary to tibialis posterior (TibPost) tendon insufficiency, failure of the ligamentous structures, or a combination of both. Aim: The aim of this study is to determine the contribution of the different medial ligaments in the development of acquired flatfoot pathology. Also to standardise cadaveric flatfoot models for biomechanical research and orthopaedic training. Methods: Five cadaveric feet were tested on a dynamic gait simulator. Following tests on the intact foot, the medial ligaments – fascia plantaris (FP), the spring ligament complex (SLC) and interosseous talocalcaneal ligament (ITCL) – were sectioned sequentially. Joint kinematics were analysed for each condition, with and without force applied to TibPost. Results: Eliminating TibPost resulted in higher internal rotation of the calcaneus following the sectioning of FP and SLC (d>1.28, p = 0.08), while sectioning ITCL resulted in higher external rotation without TibPost (d = 1.24, p = 0.07). Sequential ligament sectioning induced increased flattening of Meary's angle. Conclusion: Function of TibPost and medial ligaments is not mutually distinctive. The role of ITCL should not be neglected in flatfoot pathology; it is vital to section this ligament to develop flatfoot in cadaveric models.